Transfer of Authority Over Mineral and Coal Mining Tenure Rights - Tri Suhendra Arbani; Prasasti Amelia; Nurfaika Ishak (Indonesian Journal of Law and Islamic Law (IJLIL), 2022)
The transfer of mining licenses with the birth of the work copyright law has shifted back to the central government. There are two issues studied, namely the main basis for the transfer of authority related to the control of mineral and coal mining and the impact of the Transfer of Authority related to the Control of Mineral and Coal Mining. The research method used is a juridical normative research method with a statute approach, data analysis using a descriptive method. The results of the research are aimed at reorganizing related to the regulation of authority affairs and improving the mechanism for granting mineral and coal mining business permits so that mine management is better in the future. In addition, the transfer of authority to issue permits is carried out to realize an efficient mining licensing system, but it cannot be denied that from the wide range of mining areas and the lack of authority possessed by the regional government as the 'host' party to supervise mineral and coal mining activities, it is not impossible. maybe this will actually have an impact on the non-intensive process of monitoring, fostering, and supervising mineral and coal mining activities.